Calculation of the electrophysical properties of dispersed-filled composites - Lyukshin, Petr Aleksandrovich; Grishaeva, Natalia Yurievna; Lyukshin, Boris Aleksandrovich; Panin, Sergey Viktorovich; Bochkareva, Svetlana Alekseevna; Matolygina, Natalia Yurievna; Uzin, Grigoriy Evgenievich (Computational Continuum Mechanics, 2017)
The properties of polymeric materials can be relatively easily changed during structural modifications by introducing fillers of different nature. Meanwhile, the chemical nature of the polymeric matrix of the resulting composition remains unchanged, whereas the thermophysical and electrophysical properties of the composition, including its strain-strength characteristics, can be markedly different from the properties of the matrix. This paper considers the method of determining the effective electrophysical characteristics of inhomogeneous materials when different material phases have properties that differ by several orders of magnitude. The compositions of polymer matrices filled with electrically conducting powder materials are investigated. Electrostatic and electrical conductivity boundary-value problems for the cell periodicity of a composite material are formulated using the basic equations of electrophysics. Partial differential equations used in the mathematical model of the material in an electric field are solved by the finite element method (FEM). Analysis of the results makes it possible to evaluate the electric potential and the electric field intensity in the composite. Such effective electrophysical characteristics of the composite material as dielectric constant and specific electric conductivity are obtained by comparing the integral characteristics (electromagnetic field energy, heat loss power) of the periodicity cells of a composite and a hypothetical homogeneous material. As an example, the electrophysical properties of several composites, in particular a composite based on polyethelene (matrix) filled with metal powder (reinforced particles), are considered. In addition, a comparison of the numerical and experimental results for the silicone-based compositions filled with graphite and copper is performed.
Keywords: numerical calculation of effective characteristics; electrophysical properties; dispersed-filled material; composite material; dielectric constant; electrical conductivity